The αvβ6 integrin in cancer cell‐derived small extracellular vesicles enhances angiogenesis. Issue 1 (20th May 2020) - Krishn, Shiv Ram; Salem, Israa; Quaglia, Fabio; Naranjo, Nicole M.; Agarwal, Ekta; Liu, Qin; Sarker, Srawasti; Kopenhaver, Jessica; McCue, Peter A.; Weinreb, Paul H.; Violette, Shelia M.; Altieri, Dario C.; et al.
ABSTRACT: Prostate cancer (PrCa) cells crosstalk with the tumour microenvironment by releasing small extracellular vesicles (sEVs). sEVs, as well as large extracellular vesicles (LEVs), isolated via iodixanol density gradients from PrCa cell culture media, express the epithelial‐specific αvβ6 integrin, which is known to be induced in cancer. In this study, we show sEV‐mediated protein transfer of αvβ6 integrin to microvascular endothelial cells (human microvascular endothelial cells 1 – HMEC1); we demonstrate that de novo αvβ6 integrin expression is not caused by increased mRNA levels. Incubation of HMEC1 with sEVs isolated from PrCa PC3 cells that express the αvβ6 integrin results in a highly significant increase in the number of nodes, junctions and tubules. In contrast, incubation of HMEC1 with sEVs isolated from β6 negative PC3 cells, generated by shRNA against β6, results in a reduction in the number of nodes, junctions and tubules, a decrease in survivin levels and an increase in a negative regulator of angiogenesis, pSTAT1. Furthermore, treatment of HMEC1 with sEVs generated by CRISPR/Cas9‐mediated down‐regulation of β6, causes up‐regulation of pSTAT1. Overall, our findings suggest that αvβ6 integrin in cancer sEVs regulates angiogenesis during PrCa progression.